PENGARUH STRUKTUR KEPEMILIKAN KELUARGA DENGAN KINERJA PERUSAHAAN PADA PERUSAHAAN TERDAFTAR DI SEKTOR PERDAGANGAN, JASA, DAN INVESTASI PERIODE 2010-2015 - Simon Eric Hanjoyo; Juniarti Juniarti Juniarti (Business Accounting Review, 2018)
The aim of this study was to know whether there was a relations of family ownership and performance. This study used family ownership as main variable and 3 Control Variables of Corporate Governance, Competitive Intensity dan Leverage. The population used in this study is a company in Indonesia that have registered in Indonesia Stock Exchange. The sample of this research was 79 companies in Indonesia registered in Indonesia Stock Exchange.The data analysis technique used was the Double Linear Regression to describe the relationship of the variables. The Data processing used SPSS  24 version. The results showed that family ownership had positive and significant affect on perfomance. While Good Corporate Governance doesn’t had significant influence towards perfomance. On the other side, competitive intensity had positive and significant affect on perfomance. Furthermore, leverage had negative and significant influence on perfomance